Building Coalitions: Understanding the Process - Ruth M. Conone; Donna Brown; Russell Willis; Elizabeth B. Bolton; Lisa Guion (EDIS)
This document is FY507, Part 15 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.